Four new species of the genus Agrotera Schrank, 1802 (Pyraloidea: Crambidae: Spilomelinae) from Hainan Island - Liu, Ping; Qi, Mujie; Wang, Shuxia (Zootaxa, 2020)
Four new species of the genus Agrotera Schrank, 1802 are described from Hainan Island: A. dentata sp. nov., A. protensa sp. nov., A. aculeata sp. nov. and A. robustispina sp. nov. Photographs of adults and genitalia are provided.